Using Pictures in Teaching English to UBSI Students in Jakarta - Bobby Octavia Yuskar (Prodi Tadris Bahasa Inggris, 2022)
Abstract: This research focuses on teaching English using pictures to UBSI students. From various pictures given to the students during their English learning in one semester, only one is specifically chosen by the researcher for students’ weekly task. The picture of a family consists of parents and siblings. The scores for the weekly task are based on two criterions set up by the researcher. Those criterions are: first, basic grammar and second, sufficient vocabulary. The methodology of this research is a qualitative research investigating the use of pictures in teaching English to UBSI students by analyzing a number of theories from numerous scholars. There are two findings obtained from this research. The first finding was obtained from a table calculating the score of students’ weekly task. The second finding obtained from a figure in the form of diagram presented in three different colors interpreting students’ weekly task in percentages. There are three main performances generated from this research after received the scores from students’ weekly task. First performance is awarded to students scored 80 points or “Great” performance and marked in A. Second performance is awarded to students scored 70 points or “Well-Managed” performance and marked in B. Third performance is awarded to students scored 60 points or “Sufficient” performance marked in C. The main points from this research are: First, the pictures help students to understand the lesson well. Second, the pictures encourage students to learn English. Third, the pictures teach the students to become creative thinkers. Keywords: English, Pictures, Students, Teaching.